EVALUASI EFEKTIVITAS PENERAPAN MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Nurul Fadllillah; Baharuddin (Almarhalah: Jurnal Pendidikan Islam, 2024)
The Indonesian government is trying to improve the standard of education that has so far lagged behind. To realize the quality of education in better school-based management, local support is needed in directing, checking and assisting schools in administration and educational experience. Elementary school education is a level of education that is part of the basic education level and is the foundation of knowledge and helps children grow and develop optimally through teacher-guided learning, so that it becomes the main tool in improving the quality of human resources. The main task of education is to develop the potential of human resources (HR) through various organizations, both governmental and non-governmental. One way of regulating it is through School-Based Management (SBM), which functions as a tool to manage the essence of teaching. Internal and external services provided by the school are directly supervised. This is in accordance with the philosophy of decentralization, which provides benefits to the community and school members by allowing principals, students, parents, and teachers to be involved in decision-making in a transparent, accountable and participatory manner. School-Based Management aims to improve the quality of education by involving cooperation from various parties, including principals, teachers, parents, and other stakeholders, as well as paying attention to facilities and infrastructure, motivation, self-concept, interests, and learning independence. In implementing the essence of education, schools seek their arrangements by implementing school-based administration. The purpose of this study was to determine how effective school-based management or MBS is in overcoming problems in schools and improving the quality of education in elementary schools. Qualitative descriptive methods are one of those used in this study. The diversity of information is generated through significant web-based writing and journals.